2011
DOI: 10.3989/gya.032911
|View full text |Cite
|
Sign up to set email alerts
|

Apricot and pumpkin oils reduce plasma cholesterol and triacylglycerol concentrations in rats fed a high-fat diet

Abstract: SuMMArYApricot and pumpkin oils reduce plasma cholesterol and triacylglycerol concentrations in rats fed a high-fat diet.Non-conventional oilseeds are being taken into greater consideration because their constituents have unique chemical Apricot and pumpkin oils reduce plasma cholesterol and triacylglycerol concentrations in rats fed a high-fat diet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
3
5
0
Order By: Relevance
“…These results are consistent with many previous studies [7,10] that have indicated the vital role played by diets containing unsaturated fatty acids in improving the levels of liver enzymes. Common carp and African catfish oils have high contents of unsaturated fatty acids (oleic and linoleic acids), in addition to their good amounts of omega 3 fatty acids.…”
Section: Impact Of Common Carp and African Catfish Oils Supplementatisupporting
confidence: 83%
See 4 more Smart Citations
“…These results are consistent with many previous studies [7,10] that have indicated the vital role played by diets containing unsaturated fatty acids in improving the levels of liver enzymes. Common carp and African catfish oils have high contents of unsaturated fatty acids (oleic and linoleic acids), in addition to their good amounts of omega 3 fatty acids.…”
Section: Impact Of Common Carp and African Catfish Oils Supplementatisupporting
confidence: 83%
“…Such findings coincide with that obtained by [6,7,61,62], who found that when experimental animals feed on high-fat diets, this leads to a significant increase in both AST and ALT activities compared with animals feed on normal diets. While those results don't agree with [22]; which may be explained by different feeding period on high-fat meals, where in the current study six weeks, while in the study referred to one month only.…”
Section: Impact Of Common Carp and African Catfish Oils Supplementatisupporting
confidence: 80%
See 3 more Smart Citations